Density dependence in productivity of a North American Mute Swan Cygnus olor population - Knapik, Randall T.; Luukkonen, David R.; Winterstein, Scott R. (Wildfowl, 2019)
Mute Swans Cygnus olor were first introduced to North America in the late 19th century and were brought to Michigan, USA, by humans in 1919. Numbers in Michigan remained low throughout the 20th century but began to grow rapidly in the early years of the 21st century, reaching 17,520 by 2013. The Michigan Department of Natural Resources (MDNR) produced a policy in 2012 to have fewer than 2,000 Mute Swans state-wide by the year 2030; however, estimates of demographic parameters and information on patterns of density dependence are needed to identify the annual control level needed to achieve long-term goals. A research partnership between the MDNR, the Wildlife Services section of the US Department of Agriculture Animal and Plant Health Inspection Service, and Michigan State University was formed to investigate the patterns of density dependence in the Michigan population of Mute Swans. Nesting pair density and productivity were surveyed in 2016–2018 using fixed-wing aircraft. Extent of nesting habitat was quantified to assess the relationships between the number of nesting pairs and nest site availability. Mean productivity for nesting pairs was low (1.4 fledglings/pair) and decreased with increases in the number of nesting pairs. Productivity was inversely related to estimated saturation of characteristic nesting habitat (βˆ = –0.979, s.e. = 0.439). Mute Swan pairs nested in non characteristic habitat on sites with many nesting pairs where characteristic nesting habitat was saturated. These results suggest that habitat-meditated density dependence in productivity is occurring for Mute Swans in Michigan. As such, demographic modelling and in-field management of Mute Swans in Michigan should take into consideration the demonstrated relationships between productivity and nesting pair densities.